ALTERED SPERMATOGENESIS IN THE HYPODACTYLOUS RATS - Jirsova, Zuzana; Kucera, Tomas; Martinek, Jindrich; Liska, Frantisek; Krenova, Drahomira; Kren, Vladimir (Biomedical papers, 2004)
Germinal epithelium of seminiferous tubules in adult, infertile hypodactylous males displays significant reduction in the number of germ-line cells. Detection of apoptosis in the germ-line cells during postnatal differentiation was performed to elucidate the mechanism of the decreased number of germ cells in the testes of adult rats. Evaluation of DNA fragmentation and expression of activated caspase-3 in germ cells did not confirm marked germ cell death during the onset of spermatogenesis as a main cause of significant reduction of germ cells in Hd/Hd testes of adult males. The primary cause of spermatogenesis deffect seems to be rather associated with a disorder in the cell cycle regulation and interrelation of germ-line cells with Sertoli cells.
Keywords: Rat hypodactyly/Altered spermatogenesis/Apoptosis